Karakteristik Proses Berpikir Mahasiswa dalam Mengonstruksi Bukti Keterbagian - Patma Sopamena (MATEMATIKA DAN PEMBELAJARAN, 2017)
Assimilation outline and accommodation from Piaget is used to evaluate student’s thinks process. According to Piaget, assimilation is integration process of new stimulation through the change of old scheme or the construction or new scheme to adapt with accepted stimulation. The sampling is done by Think-Out-Loud (TOL). From results of this research is found that the process thought the student IAIN Ambon in constructing proof evidence had two characteristics, that is: (a) almost complete, that is when the student construct but proof is not in accordance with the sub-structure of the problem (the process of algebra) in the process of the assimilation and accommodation, (b) incomplete because incomplete the process of the assimilation that is the process of thinks simplest and incomplete the process of accommodation. Key word: Thinking Process, Construction, Proof